Modern state of metrological support of "digital level-barcode staff" measurement systems - Mirzaev, Anvar; Yekimov, Sergey; Khavina, Irina; Pyurko, Olga; Hlebova, Natаlia (My University, 2024)
In this work, several methods for studying measuring systems “digital level - barcode staff” are analyzed. The methods of different countries for checking means and technological schemes for monitoring the main metrological parameters of barcode strips are compared. Based on the material studied, it was revealed that metrological support for the “digital level - barcode staff” system is carried out in specialized laboratories, which is not available to every user. As a result, the study revealed that not one of the methods considered the influence of vertical refraction. Based on the research of this article, it is proposed to improve the control technique taking into account the influence of vertical refraction.
Keywords: information technology; digitalization; software; vertical refraction; geodetic metrology; atmosphere; leveling methodology